Why Multi-Family Groups for Transgender Adolescents and Their Parents? - Rabain, Nicolas S. (Frontiers in Sociology, 2021)
The author presents a therapeutic approach for contemporary families carried out in an innovative mental health care setting. This approach involves receiving both transgender adolescents and their parents. Initially, the adolescents are brought together in a discussion group. Then, the parents of these adolescents are gathered without their children in order to reflect on family relations and social adaptation and to receive support when needed. Both groups are gathered together a couple of times a year in a multi-family meeting. Using a dynamic based on the principle of free association and the interplay of identifications among participants, the author points out how these groups and multi-family gatherings promote mental health and prevent mental disorders and the disruption of family relations.